2019
DOI: 10.1177/1043454219849572
|View full text |Cite
|
Sign up to set email alerts
|

Skin Complications Associated With Pediatric Central Venous Access Devices: Prevalence, Incidence, and Risk

Abstract: Central venous access devices (CVADs) are vital to enable treatment for children with cancer and other complex health conditions. However, complications effecting the CVAD wound are commonly reported. This study aimed to identify the incidence and prevalence of CVAD-associated skin complications current management, and characteristics associated with complication development, in pediatrics. A prospective observational study performed across medical, oncology, and hematology departments at a tertiary pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…12 Common treatments include topical application of ointment or keeping the dressing application away from the injury, 11 but prevention strategies based on early risk assessment or evidence-based approaches are lacking. 13 Previous studies have primarily focused on identifying the risk factors of skin injury with PICC placement and have rarely described at what point after catheterization patients are at highest risk. Mao et al 14 found that PICC-related skin injury first occurred in patients after a mean of 33.00 ± 6.29 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Common treatments include topical application of ointment or keeping the dressing application away from the injury, 11 but prevention strategies based on early risk assessment or evidence-based approaches are lacking. 13 Previous studies have primarily focused on identifying the risk factors of skin injury with PICC placement and have rarely described at what point after catheterization patients are at highest risk. Mao et al 14 found that PICC-related skin injury first occurred in patients after a mean of 33.00 ± 6.29 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinics, skin injury is often seen as a minor problem, and PICC-related skin injury has been overlooked 12 . Common treatments include topical application of ointment or keeping the dressing application away from the injury, 11 but prevention strategies based on early risk assessment or evidence-based approaches are lacking 13 …”
Section: Discussionmentioning
confidence: 99%
“…The primary and secondary outcomes were incorporated into a secure, web-based data collection tool (Research Electronic Data Capture). The data collection tool was originally designed and trialed within the study site by Marsh et al 13 and in pediatrics by Ullman et al 14 The data collection instruments were piloted for interrater reliability and feasibility prior to use. 15 Education and familiarization with the data collection tools were provided to clinical and research staff, to ensure consistency and clarify processes.…”
Section: Data Collectionmentioning
confidence: 99%
“…
Peripherally inserted central catheters (PICCs) are widely used in chemotherapy for oncology patients (Liao et al, 2019;Santos et al, 2020).However, given that insertion sites need to be maintained using disinfectants and medical adhesives weekly (Ullman et al, 2019), the skin under a dressing becomes sensitive (Zhao, He, Huang, et al, 2018), and is prone to medical adhesive-related skin injury (MARSI), which is any skin damage associated with the use of medical adhesive products, including film dressings (Fumarola et al, 2020).Studies have shown that the incidence of MARSI at the PICC insertion sites of oncology patients is 19.70% to 31.50% (Wang
…”
mentioning
confidence: 99%